Impact of Cervical Sagittal Alignment on Axial Neck Pain and Health-related Quality of Life After Cervical Laminoplasty in Patients With Cervical Spondylotic Myelopathy or Ossification of the Posterior Longitudinal Ligament: A Prospective Comparative Study. Issue 4 (May 2018) - Fujiwara, Hiroyasu; Oda, Takenori; Makino, Takahiro; Moriguchi, Yu; Yonenobu, Kazuo; Kaito, Takashi
Abstract : Study Design: This is prospective observational study. Objective: To prospectively investigate the correlation among axial neck pain; a newly developed patient-based quality of life outcome measure, the Japanese Orthopaedic Association Cervical Myelopathy Evaluation Questionnaire (JOACMEQ); and cervical sagittal alignment after open-door laminoplasty for cervical myelopathy. Summary of Background Data: Many studies have focused on postoperative axial neck pain after laminoplasty. However, the correlation among cervical sagittal alignment, neck pain, and JOACMEQ has not been investigated. Materials and Methods: In total, 57 consecutive patients treated by open-door laminoplasty for cervical myelopathy were included (mean age, 63.7 y; 15 women and 42 men) and divided into 2 groups according to diagnosis [cervical spondylotic myelopathy (CSM) group: 35 patients, and ossification of the posterior longitudinal ligament (OPLL) group: 22 patients]. JOA score, a subdomain of cervical spine function (CSF) in the JOACMEQ, and the visual analog scale for axial neck pain were assessed preoperatively and 12 months postoperatively. Radiographic cervical sagittal parameters were measured by C2 sagittal vertical axis (C2 SVA), C2–C7 lordosis, C7 sagittal slope (C7 slope), and range of motion. Results: C2 SVA values in both groups shifted slightly anteriorly between preoperative and 12-month postoperative measurements (CSM: +19.7±10.9 mm; OPLL: +22.1±13.4 mm vs. CSM: +23.2±16.1 mm; OPLL: +28.7±15.4 mm, respectively). Postoperative axial neck pain in the OPLL group showed strong negative correlations with C2 SVA and C7 slope. Strong negative correlations were found between axial neck pain and CSF in both the preoperative CSM and OPLL groups (CSM: r =−0.45, P =0.01; OPLL: r =−0.61, P <0.01) and between axial neck pain and CSF in the postoperative OPLL group ( r =−0.51, P =0.05). Conclusions: This study demonstrated a significant negative correlation between neck pain and CSF in both the CSM and OPLL groups preoperatively and in the OPLL group postoperatively. Radiographic cervical sagittal alignment did not significantly correlate with preoperative or postoperative axial neck pain.